Disentangling the magnetic force noise contribution in LISA Pathfinder. (June 2015) - Armano, M; Audley, H; Auger, G; Baird, J; Binetruy, P; Born, M; Bortoluzzi, D; Brandt, N; Bursi, A; Caleno, M; Cavalleri, A; Cesarini, A; et al.
Abstract: Magnetically-induced forces on the inertial masses on-board LISA Pathfinder are expected to be one of the dominant contributions to the mission noise budget, accounting for up to 40%. The origin of this disturbance is the coupling of the residual magnetization and susceptibility of the test masses with the environmental magnetic field. In order to fully understand this important part of the noise model, a set of coils and magnetometers are integrated as a part of the diagnostics subsystem. During operations a sequence of magnetic excitations will be applied to precisely determine the coupling of the magnetic environment to the test mass displacement using the on-board magnetometers. Since no direct measurement of the magnetic field in the test mass position will be available, an extrapolation of the magnetic measurements to the test mass position will be carried out as a part of the data analysis activities. In this paper we show the first results on the magnetic experiments during an end-to-end LISA Pathfinder simulation, and we describe the methods under development to map the magnetic field on-board. A post-publication change was made to this article on 26 Jun 2020 to add an author.